PENGELOLAAN HUTANG DALAM KONDISI PAILIT: KAJIAN FIQH ISLAM TERHADAP HAK DAN KEWAJIBAN PENGUSAHA - Bagus Jamroji (Jurnal Ilmu Hukum, 2025)
This study examines debt management in bankruptcy conditions based on Islamic jurisprudence (fiqh), focusing on the rights and obligations of entrepreneurs. In Islam, debt is not only a financial obligation but also a moral responsibility that must be fulfilled fairly and humanely. Principles such as justice, transparency, and compassion form the foundation for resolving debts. The findings show that Islam provides flexibility in bankruptcy situations, including debt restructuring or partial forgiveness for debtors unable to meet their obligations. Islamic financial instruments like zakat and qardhul hasan, as well as fintech solutions, offer innovative approaches to debt management in modern contexts. This study emphasizes the importance of applying maqashid syariah in debt management to protect creditors' rights while considering the debtor’s condition. It provides practical insights for entrepreneurs, creditors, and financial institutions to establish a more just and sustainable economic system aligned with Islamic principles.